RANCANGAN SOLUSI PENGELOLAAN SAMPAH DENGAN KONSEP FOCUS GROUP DISCUSSION (FGD) PENTA HELIX DI KABUPATEN GARUT - Dini Turipanam Alamanda; Hadum Hadiansyah; Abdullah Ramdhani (Faculty of Social Science, Universitas Negeri Padang, 2020)
The waste problem in Garut Regency was entering an emergency and alarming stage. The situation has mobilized various elements, namely academics, entrepreneurs, communities, government and the media to take strategic steps together in overcoming the problem of waste. Garut University, especially Faculty of Social and Political Sciences (FISIP), became the initiator of the focus group discussion (FGD) agenda which subsequently developed into the Penta helix Garut Free Waste Movement. The purpose of this study was to map the solution steps taken by the Penta helix team based on the results of the FGD. This research was a qualitative type using FGD method. The FGD was attended by 28 participants consisting of 3 academic representatives, 7 company representatives, 6 community representatives, 10 government representatives, and 2 media representatives. Triangulation was carried out on the initiator's side by testing the dependability and confirmability. The results showed that there were 7 strategic issues namely technology, processing, education, economics, institutions, policies and coordination that needed to be further discussed through further FGDs. All elements were expected to continue to communicate and collaborate and could complete the discussion of the 7 issues to be used as a solution proposal to the government of Garut Regency, therefore, it could be used as material for policy formulation to solve the waste problem.